Operational risk modelling and management - Franzetti, Claudio (Boca Raton, Fl. : CRC Press, 2010)
'In banking regulation, tools are needed to quantify risk and calculate the amount of capital reserve required to mitigate such risk. This book offers a complete model for the quantification of so-called operational risks. It offers a detailed discussion on the link between modeling approaches and management, which has been neglected in the literature, as well as the mathematical modeling of the loss distribution approach. With an emphasis on risk management and management fundamentals, the text presents a complete simulation model along with tested examples that can be replicated using R software. The author provides a broad view on managing risk using this mathematical model'--
Includes bibliographical references and index.
Keywords: Risk management; Risk management -- Mathematical models